The Effect of Job Stress, Job Satisfaction and Emotional Intelligence on Turnover Intention - Kurniawan, Prasetyo; Susanto, Noto (Publisher Cv. Inara, 2023)
The purpose of this study was to examine and analyze the effect of job stress, job satisfaction, and emotional intelligence on turnover intention in employees of PT. ISS Indonesia Bintaro. Methods This research uses the causality method. The population in this study were all employees of PT. ISS Indonesia Bintaro. The number of samples used was as many as 150 respondents. Data analysis method using Partial Least Square (PLS). The results of this study are as follows: Job stress has a significant positive effect on turnover intention in employees of PT ISS Indonesia. Job satisfaction has a significant negative effect on the turnover intention of PT ISS Indonesia employees. Emotional intelligence has a significant negative effect on the turnover intention of PT ISS Indonesia employees.